Al-Faruqi’s views on selected topics of Ilm al-Kalam - Adibah Abdul Rahim,; Zuraidah Kamaruddin,; Amilah Awang Abdul Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The study of Ilm al-kalam is still relevant and meaningful in the modern period of time. It is not outdated rather it has gone through various developments throughout the history in order to cope up with the needs of the age. This paper studies a contemporary approach to ilm al-kalam by a contemporary theologian, Ismail Raji al-Faruqi. It examines al-Faruqi’s distinct approach in comparison to a classical position of ilm al-kalam. In doing so, the study focuses on selected theological issues, namely, the relationship between reason and revelation, the principle of causality, and freewill of choice. After examining those theological issues, the study found that al-Faruqi revitalized the classical position of ilm al-kalam in some respects, thus, presented it in a new dimension. It is observed that al-Faruqi’s approach to Ilm al-Kalam is very intelligible to the modern mind and to a modern age. Therefore, this study acknowledged his vital contributions in the development of ilm al-kalam.